RESPONSE OF HAWTHORN TRANSPLANTS TO BIOFERTILIZERS AND POULTRY MANURE - Al-Hadethi, M. E.A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted in lath house, Dept. of Horticulture and Landscape Gardening, Coll. of Agricultural Engineering Sciences – Univ. of Baghdad during 2017 / 2018 growing seasons to investigate the influence of biofertilizers and poultry manure on 2 year's old trees of hawthorn transplants. This study included two treatments: four types of biofertilizers control (B1), Azospirillum brasilense (B2), Bacillus megatherium (B3) and A. brasilense + B. megatherium (B4) and three levels of poultry manure , 0 (M0), 250g.tree-1 (M250) and 500g.tree-1 (M500) and their interactions. Treatments were replicated four times at factorial experiment in a RCBD. The experimental results showed that biofertilizers treatment (B4) gave the highest leaves number of 72.42 and 77.83 leaf.plant-1, highest leaf nitrogen content of 1.62 and 1.75 % and highest leaf IAA content of 34.41 and 38.85 μg g-1 FW, for both seasons, respectively. Results also showed that poultry manure at levels 500g.tree-1 (M500) was superiority on control treatment and gave the highest leaves chlorophyll content of 59.19 and 59.96 SPAD units and highest leaf GA content of 139.46 and 140.76 μg. g-1 FW, for both seasons, respectively.